2021
DOI: 10.3390/info12120497
|View full text |Cite
|
Sign up to set email alerts
|

Technology-Induced Stress, Sociodemographic Factors, and Association with Academic Achievement and Productivity in Ghanaian Higher Education during the COVID-19 Pandemic

Abstract: The COVID-19 pandemic affected many nations around the globe, including Ghana, in the first quarter of 2020. To avoid the spread of the virus, the Ghanaian government ordered universities to close, although most of them had only just begun the academic year. The adoption of Emergency Remote Teaching (ERT) had adverse effects, such as technostress, notwithstanding its advantages for both students and academic faculty. This study examined two significant antecedents: digital literacy and technology dependence. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 57 publications
0
13
1
4
Order By: Relevance
“…Considering the influence of gender on the levels of faculty technostress, about twice as many females participated in the 2021 sample (58.5%) as compared to the 2020 sample (30.9%). Previous studies have determined that females experience greater techno-complexity than their male counterparts (Çoklar & Şahin, 2011;Essel et al, 2021;Jena & Mahanti, 2014;Marchiori et al 2019). This study contradicts these findings.…”
Section: Techno-complexitycontrasting
confidence: 76%
See 1 more Smart Citation
“…Considering the influence of gender on the levels of faculty technostress, about twice as many females participated in the 2021 sample (58.5%) as compared to the 2020 sample (30.9%). Previous studies have determined that females experience greater techno-complexity than their male counterparts (Çoklar & Şahin, 2011;Essel et al, 2021;Jena & Mahanti, 2014;Marchiori et al 2019). This study contradicts these findings.…”
Section: Techno-complexitycontrasting
confidence: 76%
“…From a teaching and learning perspective, technostress can adversely influence the academic achievement and output of students in higher education (Essel et al, 2021;Upadhyaya & Vrinda, 2021). Technostress perceptions of faculty teaching in higher education pre-pandemic and during have been identified (Boyer-Davis, 2020).…”
Section: Technostress In Teaching and Learningmentioning
confidence: 99%
“…With the increasing infiltration of 21st-century technologies into classroom activities [5][6][7], the flipped classroom (FC) approach has gained traction in high school [8]. Further, the FC approach has attained popularity in recent years as a technology-supported instructional innovation that utilises the classroom period for students to actively engage in interactive learning tasks, which incorporate scaffolding and individualised feedback from the teacher, while teachers' conventional teaching approach is delivered via asynchronous video lessons outside of the class period [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…One more study in Poland reported an increase in the level of educational burnout, lower life satisfaction and less-effective coping strategies for perceived stress during the quarantine of COVID-19 by Polish students [ 28 ]. Similarly, a study on higher education students in Ghana reported the impact of technostress on the students’ academic achievement and academic productivity [ 29 ]. Given this, a study con-ducted on students from seven countries (i.e., China, Ireland, Malaysia, South Korea, Tai-wan, the Netherlands, and the United States) emphasized the importance of sleep educa-tion and resilience training in the higher education sector to enhance coping strategies and decrease the perceived stress [ 30 ].…”
Section: Introductionmentioning
confidence: 99%